Application of the K-Medoids Clustering Algorithm to Determine the Nutritional Status of Toddlers - Betrisandi, Betrisandi; Hasan, Maryam; Bahrin, Bahrin (Jambura Journal of Electrical and Electronics Engineering, 2025)
Stunting is a chronic malnutrition problem due to a lack of nutritional intake in the body for a long time, as a result of which there is a growth disorder in children, namely the child's height becomes shorter or dwarfed than the standard age. The problem of malnutrition in toddler is a major concern in various countries. Based on the data from the Ministry of Health of the Republic of Indonesia in 2018, 30.8% of Indonesian toddlers were malnourished. Malnutrition in toddlers is very influential on physical and mental growth such as intellectual intelligence, speaking, walking, learning, immune system and low body immune system. The purpose of thisstudy is to classify the nutritional status of toddler into five cluster namely cluster 0 poor, cluster 1 undernourished, cluster 2 good nutrition, cluster 3 over nutrition and cluster 4 obesity by using the K-Medoids Algorithm method. K-Medoids Algorithmis one of the Algorithm used in data and mining. K-Medoids Algorithm is relatively fast and simple, making it easier to find Medoids in a group (cluster). Based on the data on toddlers there are 74 toddlers, the results of clustering are obtained from grouping, cluster 0 is 13 toddlers with bad nutrition, cluster 1 is undernutrition 15 toddlers, cluster 2 is good nutrition 21 toddlers, cluster 3 is over nutrition 23 toddlers and cluster 4 is obesity totaling 2 toddlers.Stunting merupakan masalah kurang gizi kronis karena kurangnya asupan gizi pada tubuh dalam waktu yang cukup lama akibatnya terjadi gangguan pertumbuhan pada anak-anak yakni tinggi badan anak menjadi lebih pendek atau kerdil dari standar usianya. Masalah kurang gizi padakelompok balita menjadi perhatian utama diberbagai negara. Berdasarkan data Kemenkes RI tahun 2018 sebanyak 30,8 % balita Indonesia mengalami gizi buruk. Gizi kurang pada balita sangat berpengaruh pada pertumbuhan fisik maupun mental seperti kecerdasan intelektual, berbicara, berjalan, belajar, daya tahan tubuh serta sistem imun tubuh rendah. Adapun tujuan dari penelitian ini adalah untuk mengelompokkan status gizi balita ke dalam 5 cluster yaitu cluster 0 gizi buruk, cluster 1 gizi kurang, cluster 2 gizi baik, cluster 3 gizi lebih dan cluster 4 obesitas dengan menggunakan metode Algoritma K-Medoids. Algoritma K-Medoids merupakan salah satu algoritma yang digunakan dalam data mining. Algoritma K-medoids relatif cepat dan sederhana sehingga memudahkan menemukan medoids dalam sebuah kelompok (cluster). Berdasarkan data balita yang ada sejumlah 74 balita maka didapatkan hasil clustering dari pengelompokkan dengan cluster 0 yaitu gizi Buruk berjumlah 13 balita, cluster 1 yaitu gizi kurang berjumlah 15 balita, cluster 2 yaitu gizi baik sejumlah 21 balita, cluster 3 yaitu gizi lebih berjumlah 23 balita dan cluster 4 obesitas berjumlah 2 balita.